Impact of Savoring Ability on the Relationship Between Older Adults' Activity Engagement and Well-Being. (March 2020) - Smith, Jennifer L.; Bihary, Joseph G.; O'Connor, Dugan; Basic, Ajla; O'Brien, Catherine J.
The relationship between activity engagement and well-being can vary based on individual characteristics, and it is important to identify moderating factors to support the development and implementation of aging services. The current study examined whether the relationship between activity engagement and well-being depends on older adults' savoring ability, that is, the ability to attend to positive experiences and to engage in emotion regulation strategies to enhance positive feelings during those experiences. A total of 5, 128 older adults ( M age = 83.86 years) completed measures of activity engagement, savoring, and well-being (i.e., life satisfaction, depression, loneliness, purpose, and health). Multilevel modeling analyses revealed that activity engagement and savoring independently predicted better functioning across all well-being measures. However, savoring moderated the relationship between activity engagement and four well-being measures (life satisfaction, depression, loneliness, and purpose). Findings suggest that older adults with low activity engagement may particularly benefit from savoring-skills training to enhance their psychological well-being.